1999
DOI: 10.1177/107385849900500411
|View full text |Cite
|
Sign up to set email alerts
|

Review : Evolution of the Motor System: Why the Elephant's Trunk Works Like a Human's Hand

Abstract: The nucleus of Darkschewitsch, the nucleus accessorius medialis of Bechterew, and the parvicellular red nucleus in the mammalian mesodiencephalon fuse with each other and thus have borders that are not always distinct. These structures project topographically to the inferior olive and receive inputs from motor cortex, premotor cortex, substantia nigra, and cerebellar nuclei, which suggests that these nuclei play an important role in mammalian motor control. Furthermore, the nuclei show developmental difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Our previous studies [3] , [33] , [28] , [52] , [24] have shown that the mesodiencephalic nuclei, including the ND, NB and pNr, show developmental differences corresponding to species-specialized body parts, such as the human hand, the elephant's trunk and the whale's axial musculature system. Onodera and Hicks (1999) [52] proposed that the phylogenetically newer pyramidal tract and well-developed mesodiencephalo-olivo-cerebellar circuits “broke through” the constraints of the older rubrospinal system of the mNr and suggested that the human pyramidal system took over to provide a tonically active framework for locomotor function, rather than actually physically replacing the rubrospinal system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous studies [3] , [33] , [28] , [52] , [24] have shown that the mesodiencephalic nuclei, including the ND, NB and pNr, show developmental differences corresponding to species-specialized body parts, such as the human hand, the elephant's trunk and the whale's axial musculature system. Onodera and Hicks (1999) [52] proposed that the phylogenetically newer pyramidal tract and well-developed mesodiencephalo-olivo-cerebellar circuits “broke through” the constraints of the older rubrospinal system of the mNr and suggested that the human pyramidal system took over to provide a tonically active framework for locomotor function, rather than actually physically replacing the rubrospinal system.…”
Section: Discussionmentioning
confidence: 98%
“…Onodera and Hicks (1999) [52] proposed that the phylogenetically newer pyramidal tract and well-developed mesodiencephalo-olivo-cerebellar circuits “broke through” the constraints of the older rubrospinal system of the mNr and suggested that the human pyramidal system took over to provide a tonically active framework for locomotor function, rather than actually physically replacing the rubrospinal system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the red nucleus, which is part of a group of premotor structures in the mesodiencephalic junction [31], contributes to the production of twitches while also receiving reafference, suggesting that the integration of motor output and sensory feedback occurs even within this so-called motor nucleus [32]. It also notable that the nuclei within the mesodienchephalic junction are associated with the evolution of limbs and flapping fins, and appear to have been differentially recruited across species for the control of highly specialized structures such as the human hand and the elephant’s trunk [33]. Twitching, it seems, is enmeshed within the neural machinery that gives limbs their purpose.…”
Section: Sleep Myoclonic Twitching and Embodimentmentioning
confidence: 99%
“…In human both RN parts are completely independent, whereas, in lower mammals the parts are essentially homogeneous 29 . The evolution-derived transition from the rubrospinal to the corticospinal tract towards bipedalism might explain the spontaneous recovery of parkinsonian symptoms in quadruple species who still uses the rubrospinal system for motor control 30,31 . Another important factor in species differences for the expression of parkinsonian symptoms might be the differences in dopamine innervation of the thalamus that is abundant in the primate and only rudimentary in rodents 32 .…”
Section: Discussionmentioning
confidence: 99%